“Necesidad de Incorporar en la Ley de Seguridad Social lo Relacionado al Derecho Laboral y Seguridad Social de las Trabajadoras Sexuales en el Ecuador” - Morocho Erazo, Erick Javier (2023)
The socio-working conditions experienced by sex workers in tolerance centers are perceived as a result of a lack of labor rights. The fact of not having a social security, added to several factors of precariousness, insecurity, inequality and discrimination, allow the largest percentage of people who are engaged in sexual service can not perform their work like any other worker according to the provisions of our Ecuadorian legislation and therefore are limited in rights and opportunities within the workplace. This reality that is lived day by day increases even more due to the lack of recognition as a job and the status that society has given to women sex workers. The objective of this research is the analysis of the current problem regarding the rights and obligations of sex workers who work in the centers of tolerance, it is also emphasized in a reform proposal that allows the real exercise of their constitutional and labor rights. For this purpose, a mixed methodological design has been used, applying a quantitative instrument, such as surveys conducted through the GoogleForms tool and a qualitative technique through interviews directed to several legal professionals specialized in different areas of knowledge, in order to obtain relevant information and data about the sexual problem in our country. The conclusions of the research are closely related to the perceptions of different professionals regarding the legality of sex work, about which there is considerable concern because this reality harms and affects the rights and labor guarantees of those women who exercise sexual activity as a form of work. Finally, a legal reform bill is proposed to the Social Security Law to contribute to the recognition of this work and to grant membership in the Compulsory General Insurance for this group of workers.